Visual assessment of structure of clayey soils under long-term no-tillage in Thohoyandou, South Africa - Phefadu, Kopano Conferance (My University, 2024)
Soil structure is described as a complex and dynamic soil property, partly related to inherent characteristics of particle size and clay mineralogy and also anthropogenic influences related to land use and management. Tillage management systems influence several soil structural properties such as reduced pore volume and size due to compaction, which on the other hand may affect the soil-water and air relation. Soil structure is regarded as one of the key soil quality indicators, thus, its evaluation and monitoring should be emphasized in soil management and conservation. Soil quality is generally based on the approaches that focuses on the inherent soil properties or human management effects. Soil quality is strongly linked to soil structure, because poor quality soil structure may lead to problems such as susceptibility to compaction, erosion and desertification. Visual soil structure quality methods for soil quality assessment such as visual evaluation of soil structure (VESS) are effective for controlling and monitoring the soil functions for sustainable agriculture. VESS is a cheap and simple field evaluation method which is used to rate soil structure quality based on related parameters such as size and appearance of aggregates, visible porosity, and roots. Qualitative measurements of related parameters like pore characteristics, aggregate stability, aggregate size distribution, bulk density, organic carbon and unsaturated hydraulic conductivity were done to validate the outcome of VESS and effect of tillage. Tillage has a direct effect on the transformation of soil structure. The impacts of the duration of no-tillage (NT) are still not yet well elucidated especially on clayey soils. The aim of the study was to visually assess the structure dynamics of the soils with relatively high clay content and profiling related structural parameters, under long term no-tillage systems in a subtropical climate. The study was carried out in Tshivhilwi and Dzingahe, Thohoyandou, Vhembe district, Limpopo Province, South Africa. The no-tillage fields in Tshivhilwi and Dzingahe were 8 years (short-term) and >40 years (long-term) respectively. Soil samples were collected and field measurements of the related parameters were done in three fields in each study area, namely: no-tillage, conventional tillage and virgin field. Five sampling points were randomly selected in a portion (area = 1000 m2) of each field per location considering the homogeneity of the soil. Soil sampling depths were 0 – 30 (topsoil) cm and 30 – 60 cm (subsoil). VESS method was used to assess the topsoil structure quality, whereas SubVESS method was used to assess the subsoil structure quality. The collected data were subjected to analysis of variance (ANOVA), multivariate analysis of variance (MANOVA) and Person correlation coefficient analysis at a 95% confidence interval (p ≤ 0.05) using IBM SPSS statistics 29.0 statistical software. A focussed literature review carried out in this study showed that there is little research on the adoption of VESS by the intended end users, which are the land managers and farmers. It also revealed a gap on the application and effectiveness of the VESS method to distinguish the impact of long-term no till systems on the soil structure quality. The assessment of soil soil structure with the VESS method in long-term no-till systems revealed that: The VESS method is effective for assessing soil structural quality in routine soil characterisation. However, it must be noted that most soil structure attributes tend to be soil and site specific. The VESS and subsoil visual evaluation of soil structure (SubVESS) scores indicated poor structure for topsoil and subsoil in NT and conventional tillage (CT) at Tshivhilwi. At Dzingahe the topsoil structure quality was fair in NT and poor in CT while subsoil structure quality was moderately good in NT and poor in CT. The bulk density was relatively lower (1.20 – 1.57 g/cm3) showing that the soils were not compacted. Organic carbon was between 1.50 and 2.00% except at Dzingahe in the 0 – 30 cm soil depth where it was above 2.00%. The assessment of pore characteristics, CO2 efflux and unsaturated hydraulic conductivity of soils under long term no-tillage system showed that no-tillage had a higher total porosity and estimated pore connectivity than CT quantified with X-ray computed tomography, although at Dzingahe total porosity in the topsoil was about 1% higher in CT. The volume of micropores increased with depth. Cracks larger than 5 mm constituted highest percentage of the total pore volume due to the high percentage of active clay. Conventional tillage had almost three times higher unsaturated hydraulic conductivity than NT at Tshivhilwi. Carbon dioxide efflux increased with soil moisture content and it was more in during the wet and dry season. The effect of no-till duration on soil aggregate size distribution, stability and aggregate associated carbon revealed that macro-aggregates (0.212 – 2 mm) constituted the largest proportion of aggregates with percentage contribution of > 60% in the short-term and long-term no-tillage system. Mean weight diameter (MWD) was greater in NT and CT in the short term and long-term no-till respectively. Subsoil indicated a more stable structural stability than topsoil. However, when comparing NT only in the two periods MWD was greater in the short term. All aggregate fractions contained more organic carbon in the topsoil but micro-aggregates had higher organic carbon than all of them in both short-term and long-term no-till systems. In conclusion, although there were some inconsistencies between the tillage systems, duration and soil depths, overall NT showed better results than CT. No-tillage has a potential to sustain good soil structure and related parameters. Frequent monitoring of soil structure induced by NT is required to detect any changes that may lead to degradation, and this can be achieved by using VESS as the monitoring tool
Thesis (Ph.D. (Soil Science) -- University of Limpopo, 2024
Keywords: Tillage; Soil structure; Soil depth; Soil quality; VESS; SubVESS; No-tillage; Soil depth; Soils -- Quality; Soil structure; Clay soils